Perkembangan Spasial di Desa Pengotan - Bangli - Djaja Bharuna S, A A Gde (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 4 No 1 (2017): April 2017, 2017)
Pengotan is one among several Bali Aga communities of Bangli Regency which had settled before Majapahit influence reached the Bali Island. This community offers unique attributes that distinguish it from other villages. In exploring its distinctive features, this study investigates the physical elements of Pengotan houses, namely: 1) forms and shapes; 2) scales and measurements; 3) materials, colors and textures; 4) structure and constructions; and 5) arts and decorative elements. Data collection of this research was done by a physical site observation supported by a series of interviews organized with several key informants. The study found that Pengotan community members maintains the original pattern of their settlement. Pengotan community however fails to look after their homes as they do not live within. Since the importance of these homes is fully acknowledged, especially during the times of ritual practices and ceremonies, it is fundamental to find out as to how their existence can be preserved. This is the ultimate goal of this study. Keywords : development, spatial structure, uniqueness, village morphology, Bali Aga